Effect of Annealing on the structural, surface morphology and optical properties for CdO:PbO composite thin films - Rasha Hamid; Maad Mohammed (Al-Qadisiyah Journal of Pure Science, 2021)
Thin films of pure cadmium oxide films (CdO) and composite with lead oxide (PbO) at different atomic ratios were prepared by pulsed laser deposition under vacuum usingpulsed laser of ND-YAG from CdO and CdO:PbO targets. The prepared thin films were characterized by different technique before and after annealing. The X-ray diffraction shows polycrystalline structures of cubic CdO phase convert tosample of mixed phases for composites. The AFM images illustratedecreasing the particle diameter and increasingsurface roughness with increasing the PbO ratio in composite. While, annealing cause to increase the particle size and reduce roughness. The optical absorbance increased with the PbO ratio, while the absorbance decreased with annealing. The energy gap reduced after annealing and increased with increasing the molar ratio of PbO. These variation in some fundamental properties of the prepared thin films by simplyvarying the components of the started target show the possibilityof controlling the properties of the prepared thin films by pulsed laser depositionfor use in many fields.